Avaliação diagnóstica dos métodos Elisa e quimiluminescência como testes de triagem alternativos à imunofluorescência indireta para a detecção de anticorpos antinucleares - Fabiano de Almeida Brito (2012)
Detection of antinuclear antibodies (ANA) plays an important role in the diagnosis of autoimmune rheumatic diseases(ARD). Different methods such as indirect immunofluorescence on HEp-2 cells (HEp-2 IIF), ELISA and chemiluminescence can be used for ANA testing, although HEp-2 IIF is considered the gold standard. The goal of this study was to evaluate the diagnostic accuracy of three commercially available ELISA kits and one chemiluminescente kit for ANA detection,with different principles andantigenic composition, and to verify the possibility of using them as an alternative to the IIF method, considering the clinical diagnostic accuracy as the standard.We evaluated 143 patients with established diagnosis of ARD (group 1), 166 patients with infectious diseases and other rheumatic diseases (group 2), 89 patients with suspicion of ARD (group 3) and 134 healthy subjects (group 4). The sensitivity of the tests, given in group1 was 87.4% for IIF and 62.9% to 90.0% for the other kits. The specificity of the tests, given in group 2, was 72.3% for IIF and 45.2% to 90.4% for other kits. The agreement with the IIF test ranged from regular to moderate. Areas under the ROC curve of the tests were not significantly different from the IIF. The frequency of positive results of IIF HEp-2 in group 4 was 13.5%, compared with frequencies of 6.0% to 36.0% for the other tests, and a 1:160 dilution was defined as "abnormal title". In group 3, the sensitivity and specificity of IIF was 92.0% and 57.8%, while the other tests ranged between 76.0% and 100% and 26.6% and 89.1%, respectively. Some ELISA kits have comparable or superior diagnostic sensitivity to HEp-2 IIF and could be used as an alternative methodfor ANA screening. Positive samples should be submitted to IIF for confirmation of results, determination of the title and the fluorescence pattern. Due to differences in sensitivity between the kits, it is essential that a careful clinical validation is performed prior to their introduction into the diagnostic routine.